FIFA Initiatives Improved Survival After Loss of Consciousness During Football Games - Katsigiannis, Sotirios; Maai, Nader; Patsalis, Polykarpos; Groppa, Sergiu; Gousias, Konstantinos; Pintea, Bogdan (Sports Medicine International Open, 2024)
Loss of consciousness (LOC) during football games is associated with very high mortality rates. In order to address football medical emergencies, in 2013 FIFA implemented the “FIFA 11 steps to prevent sudden cardiac death” program and distributed the FIFA Medical Emergency Bag. The purpose of this work was to identify independent survival factors after LOC on the pitch and to investigate the effectiveness of the FIFA initiatives. An internet search was performed to identify football players suffering LOC on the pitch between 1990 and 2021. A total of 268 cases could be identified and were dichotomized according to the implementation date of the FIFA medical emergency bag. There was 55% mortality after LOC, while cardiogenic LOC was more often (82% vs. 20%) fatal than traumatic LOC. Mortality in developing countries was higher than in developed countries. From the year 2013 survival improved significantly for both traumatic and cardiogenic cases. The location of the LOC significantly influenced survival (OR: 0.20 and p<0.001). LOC on the football field is associated with increased mortality and requires separate monitoring based on a traumatic vs. non-traumatic cause. FIFA initiatives significantly reduced mortality after LOC but significant differences were identified between developed and developing countries.
Keywords: loss of consciousness; football; FIFA medical emergency bag; FIFA 11 program; trauma; sudden cardiac death